Ocular Manifestations of Goldenhars syndrome- A case series - Wadhwani, Meenakshi; Kursange, Shubhangi (Nepalese Journal of Ophthalmology, 2021)
Goldenhars syndrome also known as facio auriculo vertebral dysplasia or first and second arch branchial syndrome has a prevalence of 1:3500 births to 1: 7500 births with male predisposition. We hereby present a case series of children presenting with Goldenhars syndrome.